Ways to Improve the Preparedness of Students to Simulate a Safe Educational Environment - Salimova Shahlo Sayfulloevna (International Journal on Integrated Education, 2023)
this article is devoted to the research and development of effective methods for improving the preparation of students for the process of modeling a safe educational environment. Addresses current security challenges and requirements in educational institutions and offers specific strategies and tools aimed at developing students’ skills in analyzing, designing, and implementing secure educational environments.